An ERP Study on Attraction Effects in Advanced L2 Learners - Bian, Jing; Zhang, Hui; Sun, Chongfei (Frontiers in Psychology, 2021)
We used event-related potentials (ERPs) to examine whether late advanced second language (L2) learners can acquire native-like sensitivity of attraction. The results revealed that L2 learners showed qualitatively similar ERP patterns with native English speakers, in that ungrammatical verbs following singular attractors, relative to their grammatical counterparts, elicited a P600, whereas this positivity was replaced by a N400 when plural attractors intervened between the subject head nouns and the verbs. However, there was a quantitative difference between two groups given that the amplitude of P600 elicited by L2 learners was smaller than that of native speakers. Subsequent individual analyses showed that both groups’ brain responses varied along a N400-P600 continuum; as one effect increases, the other decreases to a similar degree. We proposed that these two ERP components represented two processing routes of agreement: the P600 indexed full, combinatorial process which parsed morpho-syntactic features between agreement controllers and targets, while the N400 indexed a shallow, heuristic process which evaluated lexical associations between agreeing elements. Moreover, similar to native speakers, L2 learners also showed an asymmetrical pattern of attraction, in that plural attractors interfered with ungrammaticality at disagreeing verbs, but they did not cause any difficulties in processing grammatical sentences at agreeing verbs. The overall results revealed that L2 processing of complex agreement with attractor interference was shallower than that of native processing and therefore, and thus late advanced L2 learners could not achieve native-like attraction effects.